1995
DOI: 10.1073/pnas.92.17.7637
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive phosphorylation of I kappa B alpha by casein kinase II.

Abstract: The NF-acB/Rel proteins are sequestered in the cytoplasm in association with the phosphorylated form of IKBa. Upon induction with a wide variety of agents, the activity of NF-KcB/Ret proteins is preceded by the rapid degradation of IucBa protein. We report the identification and partial purification of a cellular kinase from unstimulated or stimulated murine cells, which specifically phosphorylates the C terminus of IKBa. There are several consensus sites for casein kinase II (CKII) In the C-terminal region of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(121 citation statements)
references
References 36 publications
3
118
0
Order By: Relevance
“…PEST sequences have not yet been identified with a particular pathway of proteolysis, so it is possible that CKII phosphorylation can affect either the ubiquitin-or trypsin-mediated forms of degradation [21]. As noted above, specific phosphorylation of cactus by CKII is consistent with reports that mammalian ΙκΒα is a substrate for this enzyme [8]. It appears that CKII phosphorylation has been conserved in evolution, further indicating that it has a functional significance.…”
Section: Lc Packman Et Alifebs Letters 400 (1997) 45-50supporting
confidence: 71%
See 1 more Smart Citation
“…PEST sequences have not yet been identified with a particular pathway of proteolysis, so it is possible that CKII phosphorylation can affect either the ubiquitin-or trypsin-mediated forms of degradation [21]. As noted above, specific phosphorylation of cactus by CKII is consistent with reports that mammalian ΙκΒα is a substrate for this enzyme [8]. It appears that CKII phosphorylation has been conserved in evolution, further indicating that it has a functional significance.…”
Section: Lc Packman Et Alifebs Letters 400 (1997) 45-50supporting
confidence: 71%
“…Fax: (44) (1223) 333345. E-mail: njgll@mole.bio.cam.ac.uk Recently, it has been shown that IKBOC is phosphorylated constitutively by casein kinase II (CKII) at 4 sites in the PEST protein stability sequences (Ser 283 , Ser 289 , Ser 293 and Thr 291 ) [8][9][10][11]. These phosphorylation sites are conserved in the equivalent sequences of cactus and may be required for signal-induced dissociation of the heterotrimeric dorsal/cactus complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The third signaling pathway is classified as atypical because it is independent of IKK, and is activated by UV and doxorubicin, both of which cause DNA damage [105]. UV radiation induces IκBα degradation via the proteasome, but the targeted serine residues are located within a C-terminal cluster, which is recognized by the p38-activated casein kinase 2 [8,68,83]. Oxidative stress also leads to NF-κB activation via IκBα tyrosine phosphorylation [55].…”
Section: Nf-κb Signaling Pathwaysmentioning
confidence: 99%
“…The phosphorylation-defective mutants IKK-1 SS/AA and IKK-2 SS/AA (Mercurio et al, 1997), and the pMT2T-IkB-a and pMT2T-RelA (Brown et al, 1995) are as described. The dominant-negative (dm) IkB-a 3C/2N-IkBa, SS/AA, and RR/LL have been described elsewhere (Barroga et al, 1995;DiDonato et al, 1996). The dn TAK1-K63W (Yamaguchi et al, 1995) was a kind gift of Dr Sakurai (Tanabe Seiaku Co., Osaka, Japan).…”
Section: Plasmids and Adenovirusesmentioning
confidence: 99%